2009
DOI: 10.1371/journal.pone.0006617
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Differences in Cortical Neurons from a Pair of Monozygotic Twins Discordant for Alzheimer's Disease

Abstract: DNA methylation [1], [2] is capable of modulating coordinate expression of large numbers of genes across many different pathways, and may therefore warrant investigation for their potential role between genes and disease phenotype. In a rare set of monozygotic twins discordant for Alzheimer's disease (AD), significantly reduced levels of DNA methylation were observed in temporal neocortex neuronal nuclei of the AD twin. These findings are consistent with the hypothesis that epigenetic mechanisms may mediate at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
170
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(185 citation statements)
references
References 25 publications
14
170
0
1
Order By: Relevance
“…Recently, a study in a pair of monozygotic twins revealed the importance of DNA methylation in a discordant case of AD (Mastroeni et al 2009). The AD twin had significantly lower amounts of DNA methylation in the neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study in a pair of monozygotic twins revealed the importance of DNA methylation in a discordant case of AD (Mastroeni et al 2009). The AD twin had significantly lower amounts of DNA methylation in the neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…87 AD patients have been further characterized by a decrease in brain SAM levels, 88 and, concomitant with this, temporal neocortex neuronal nuclei were found to be hypomethylated in a patient with AD compared to his non-AD monozygotic twin. 89 5hmC, which exists at high levels within the brain, has also been implicated in AD, inferring a potential involvement of demethylation with neurodegeneration. 90 In accordance with this possibility, a single nucleotide polymorphism in the gene encoding TET1 (rs5030882) was reported to be associated with late-onset AD.…”
Section: Aberrant Methylation In Noncancerous Diseasesmentioning
confidence: 99%
“…Three catalytically active enzymes, DNA methyltransferase1 (DNMT1), DNMT3a, and DNMT3b, have been identified for the establishment and maintenance of DNA methylation patterns in mammalian cells. Pathologically altered DNA methylation has been described in various cancers (13,14), and its role is starting to be revealed in many other diseases such as multiple sclerosis (15), Alzheimer's disease (16), and systemic lupus erythematosus (17). However, the role of different DNMTs in regulation of skeletal muscle atrophy program remains completely unknown.…”
mentioning
confidence: 99%